Composition transformation of terrigenous organic matter resinous-asphaltene components in super-deep wells in Siberia during meso- and apocatagenesis - K. V. Dolzhenko; L. S. Borisova; A. N. Fomin; I. D. Popova (Georesursy, 2024)
The evolution of the elemental composition of dispersed organic matter (DOM) heterocyclic components during catagenesis was traced via studying samples from the Tyumen (SG-6) and Srednevylyuy-27 (SV-27) super-deep wells of Siberia. During mesocatagenesis, the composition of terrigenous DOM asphaltenes and resins undergoes directed changes: a decrease in hydrogen and oxygen content, enrichment with carbon, and graphitization of the structure. During apocatagenesis, due to high-temperature destruction, on the one hand, there is a condensation of individual blocks of asphaltenes and their transition to an insoluble form (formation of epiasphaltenic kerogens – EPAK). On the other hand, the lighter part of the asphaltenes goes into the formation of hydrocarbons and gas formation – a relative increase in the concentration of the former in % by mass of residual bitumoids is noted, as well as structural redistributions within benzene and spirit-benzene resins. In all studied parameters of the elemental composition, a symmetrical (unidirectional) transformation of resinous and asphaltene components of bitumoids from the SG-6 and SV-27 wells under harsh thermobaric conditions is noted. The obtained results should be taken into account when predicting new oil and gas accumulation zones in deep-laid horizons.